Characterisation of RSV infections in children without chronic diseases aged 0–36 months during the post-COVID-19 winter season 2022/2023 - Meier, Katharina; Riepl, Angela; Voitl, Peter; Lischka, Lena; Voitl, Julian J. M.; Langer, Klara; Kuzio, Ulrike; Redlberger-Fritz, Monika; Diesner-Treiber, Susanne C. (Frontiers in Pediatrics, 2024)
Background: Respiratory syncytial virus (RSV) is one of the leading causes of hospitalisation, morbidity, and mortality due to respiratory infection in the first years of life. This longitudinal prospective study outlines the 2022/23 season`s viral patterns in Austria after the epidemiological changes determined by public health measures.We aimed to highlight differences within the RSV subtypes and genotypes in 0-36month-old children without chronic diseases in the outpatient setting.Methods: From November 2022 to March 2023 children younger than 36 months admitted to Vienna`s largest paediatric primary healthcare centre with an acute respiratory infection were enrolled in this study. Nasal swabs and multiplex PCR panels detected 20 viruses including RSV subtypes and genotypes. Clinical presentation, features, and treatment of the participants were documented and analysed using the Modified Tal Score (MTS). Patients were scheduled for a telemedical follow-up one week after the initial appointment. Analysis was done using descriptive statistics, including Cramér V and binominal logarithmic regression.Results: Among the 345 samples from 329 children, RSV was the most common virus (31.9%), followed by influenza (17.5%) and rhinovirus infections (20.58%). Of the RSV positive samples, only 13 cases were RSV subtype A (11.8%), whereas 97 were of subtype B (87.3%); ON1 and BA9 were the only detectable RSV genotypes (ON1: BA9=1:9.25). RSV was the main predictor of hospitalisation (OR 7.5,, and age had a significant but smaller effect (OR 0.89, 95%CI (0.81-0.99).Almost all patients' clinical status improved within the first days.RSV cases showed a rapid onset in late November 2022, and subtype B was predominant throughout the season. RSV infection was associated with higher hospitalisation rates, even after excluding high-risk patients (preterm and severe chronic diseases population).Further testing in the upcoming winter seasons will improve our knowledge of the dominant subtype and its association with disease severity, especially with the development of novel RSV vaccine candidates.